OPTIMASI PENEMPATAN TITIK ODP PADA JARINGAN FTTH DI PERUMAHAN GRAHA DEWATA MALANG MENGGUNAKAN ALGORITMA K-MEANS CLUSTERING - Yahya, Muhammad Izzuddin; Kusmaryanto, Sigit; Partiansyah, Fakhriy Hario (Jurnal Mahasiswa TEUB, 2026)
The increasing demand for high-speed internet accessdrives service providers to develop efficient and reliable Fiber to theHome (FTTH) networks. One of the key challenges in FTTH planningis the optimization of Optical Distribution Point (ODP) placement,since suboptimal positioning may cause unequal cable distributionbetween different Optical Network Terminals that are assigned to thesame ODP. This study proposes an approach to optimize ODPplacement using the K-means clustering algorithm, with the objectiveof identifying cluster centers that represent optimal ODP locations.The algorithm groups customer coordinates into clusters, whiledifferent values of K are tested to determine the configuration thatyields the most efficient and balanced ODP utilization. This approachaims to reduce the disparity of noise during transmission betweenONTs in the same cluster.Keywords: FTTH, ODP, K-means clustering